Spatiotemporal evolution and driving factors analysis of carbon stock in traditional industrial transformation region: a case study in Harbin and Changchun urban agglomeration, China - Zhi, Rui; Lin, Lin; Yang, Xu; Zhang, Jingxiao; Shao, Jinggan; Xu, Xiangdong (Frontiers in Environmental Science, 2025)
Driven by a series of policies, the rapid urban expansion and industrial transformation of the Harbin and Changchun Urban Agglomeration (HCUA), has altered the original land use structure, adversely impacting the ecological environment. This has consequently affected regional carbon storage.In the present study, a theoretical evaluation model of dynamic change of carbon stock based on land use type was established, which linked PLUS, InVEST, geographic detector and geographical weighted regression model to analyze the evolution of land use and carbon stock in the process of industrial transformation. The findings revealed that cultivated and forest were the predominant land types within HCUA. Over these 2 decades, HCUA experienced a decline in carbon stocks by 1.74%, resulting in an overall reduction of 87.02 Mt to reach 4902.63 Mt by 2020. Natural factors primarily shape the spatial distribution of carbon stocks. The amount of carbon stored in each scenario is reduced by 2040. The SD scenario is characterized by its exceptional capacity for carbon storage (4882.06 Mt).